Translating time: chronicle, prognostication, prophecy. Issue 1 (February 2015) - Green, Jonathan
<x xml:space="preserve">Abstract</x> The early modern period knew two kinds of writing about time: writing the past, and writing the future. Chronicles, as exemplified by the Nuremburg Chronicle of Hartmann Schedel and his associates printed in 1493, might entail mobilizing the intellectual talents of a city's patrician elite in order to import Italian humanist historiography north of the Alps, and then from Latin into the vernacular. Astrological prognostications, of which thirty or more editions might be published in a given year, represent the meeting of scientific and popular discourse, while prophetic pamphlets belonged firmly to the popular realm. In this article, I demonstrate how, in each of these genres, translation was a creative rather than a derivative activity, one that drove development in the genre and brought forth printed works of new kinds. For the chronicle, translation created a history writing that was aware of its own print media context; for prognostications, translation created the characteristic form of the printed booklet still known as the Practica teüsch long after Latin prognostications were all but unknown; and for prophecies in print, translation was a constitutive part of their origin and transmission as texts: to become a prophecy, a text had to be translated from one medium, one era, one context, or one language into another.